Hard Outside and Soft Inside: Laser‐hardening of components subject to wear in series. Issue 2 (12th April 2017) - Schumann, Detlef; Leipe, Peter
Abstract: As to complex component geometries and components subject to wear — for which conventional hardening techniques often fail —, the laser‐beam hardening process nowadays offers new solutions to create wear‐resistant surfaces. In particular, curved and surfaces that are difficult to access, holes as well as components that easily warp can be efficiently hardened by means of laser. The challenges and solutions for series production are exemplified here by a component used in diesel injection technology.